Evaluation of Chemical for Sand Consolidation in Laboratory Scale - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2020)
These paper contains a highlight of laboratory experiment to evaluate the work of chemical for sand consolidation to strengthen the bonding between grains of rock while do not cause permeability reduction significantly. This experiment used reservoir rock and fluids to understand the interaction between the chemical solution and the reservoir rock and fluid. Firstly, the reservoir rock and fluid were analyzed their properties. The rock has been analyzed using CT Scan to drill the best representative core plug for the experiments, using SEM to identify the pore throat and pore geometry of the rock, using XRD to determine the minerals composition which mostly quartz. While the fluids have been analyzed for the anions and cations content, viscosity and other important properties. The brine particle content and also particle size distribution of the rock have been also over lied in the graph in order to know the possibility of bridging particle in the pore throat, but the graph looks good that no problem may arise from the bridging particle. Chemical for Sand Consolidation has been used in this experiment. Sand consolidation chemical normally contain plastic resin that has a property of bonding between solid materials. It sticks on the surface of solid materials and bonding together.The core flooding experiments have been run for 4 times, 2 times using synthetic cores and the other two using native cores. The experiments used synthetic cores reduce the permeability significantly. However, after cutting both ends of the core the permeability has indicated improvement. The other 2 experiments using native cores have reduced the permeability approximately 4 times down. The last two experiments have no cutting the ends of core for further experiments, so they cannot be compared to the first two experiment. So, the experiment procedures must be improved for the next evaluation, such as during curing time the rate of injected oil may be increased to reduce the adsorption of chemical to the surface area of the pore and also to hinder the flocculation of chemical in the pore space.